Sherlock's diseases of the liver and biliary system - Dooley, James (James S.); Lok, Anna S.F; Burroughs, Andrew K.; Heathcote, E.Jenny; Sherlock, Sheila, Dame (Wiley-Blackwell, 2011)
This brand-new edition, now named Sherlock's Diseases of the Liver and Biliary System, after the late Professor Dame Sheila Sherlock, continues to provide concise clinical guidance for all those treating patients with hepato-biliary disease. Enabling clinicians to formulate incisive diagnoses and appropriate treatment strategies, this book has been updated to reflect the advances that have been made in the last 10 years, providing didactic and reliable clinical guidance in hepatology from the world's leading experts. A consistent chapter structure allows readers to access the information immediately, with summary boxes and key learning points throughout, and special emphasis on the latest in evidence-based clinical guidance